Rancang Bangun Sistem Pakar Psikologi Umum menggunakan Metode Forward Chaining - Fahmi Fadlillah; Ade Sutedi; Yoga Handoko Agustin; Deni Heryanto (Jurnal Algoritma, 2022)
The development of the medical world at this time involves a lot of computers to help diagnose a disease. especially psychology has used technology in practice. Psychological disorder is a condition that affects the human mind characterized by erratic behavior, mood swings, and mental disorders that are not considered part of normal human development. This study aims to produce a web-based expert system that can be used by the public with the supervision of psychologists to diagnose psychological disorders who are able to make decisions according to the rules. The inference engine used is the forward chaining method and the methodology used in the development of this application is the Ratinoal Unified Process (RUP) using the stages of inception, elaboration, construction. The model and design in this study uses the Unified Modeling Language (UML). The result of this research is a Web-Based General Psychology Expert System Design Using Forward Chaining Method.